Management of higher education for intellectual capital of company formation - Garnyk, Liudmyla Petrivna; Snihurova, Irina Ivanivna (Національний технічний університет "Харківський політехнічний інститут", 2018)
Culture determines and creates educational content, its concepts and methodology. Readiness and responsibility to deconstruction of traditional beliefs, viewpoints and practices that are getting to compromise threw common human values have formed fundament of philosophy of modern education. Great influence on establishment of intercultural formal and non-formal education as like as its philosophy was made by global corporate development with its main strategic resource - knowledge - generated by socially and culturally flexible highly qualified experts. In our research we made attempt to observe main turning points of formation and further development of contemporary intercultural education paradigm in relation with trends of social and economic development in global and postmodern philosophy of education contexts.

Культура визначає і створює зміст освіти, її концепції та методологію. Готовність і спроможність до трансформації традиційних уявлень, світоглядів і практик, які досягають компромісу, апелюючи до загальнолюдських цінностей, сформували фундамент філософії сучасної освіти. Значний вплив на виникнення інтеркультурної формальної та неформальної освіти так само, як і їх філософії, було здійснено розвитком глобалізації, зокрема через її головний стратегічний ресурс - знання - згенероване соціально та культурно мобільними висококваліфікованими експертами. У цьому дослідженні ми здійснили спробу оглянути головні чинники формування та подальшого розвитку сучасної парадигми інтеркультурної освіти, зважаючи на її зв'язки з трендами соціального та економічного розвитку в контекстах світової та постмодерної філософії освіти.
Менеджмент вищої освіти для формування інтелектуального капіталу компанії
Keywords: educational management; intellectual capital of company; higher education; культура; сучасна освіта; навчальний процес